Olimp i Polska. Religia w "Stefanie Czarnieckim" Kajetana Koźmiana - Zabielski, Łukasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
Kajetan Koźmian (1771-1856) is a representative of the 19th century classicism called post-partition or Warsaw classicism. Similarly to other Polish and European poets, he made an attempt to create a national epic. His work titled "Stefan Czarniecki" is considered to be the first national epic. It was published in 1858 in Poznań. This monumental poem has 500 pages and almost 13 thousand verses. This ambitious classic writer from Piotrowice aspired to become a national poet. He desired to follow two masters of literature, namely Virgil and Horace. Frankly, I think that Koźmian failed. He could not write a national epic and remain faithful to his ancient idols at the same time. This article analyses the reasons for this fiasco. Generally, they are the antinomies between Christian beliefs on the one hand, and Greek and Roman mythologies on the other.
Olympus and Poland. Religion in Kajetan Koźmian's "Stefan Czarniecki"
Keywords: klasycyzm porozbiorowy; epopeja narodowa; wątki religijne; Koźmian; Wergiliusz; Tasso; Homer; post-partition classicism; national epic; religious topics; Virgil